Determinasi Kinerja Karyawan: Menguji Peran Komitmen Organisasi sebagai Pemediasi Hubungan Gaya Kepemimpinan dan Reward Studi pada PT CJ Feed and Care Plant (Divisi Packing) - Luthfi Arie Widzayanto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the influence of leadership style and reward on employee performance, with organizational commitment as a mediating variable at PT CJ Feed and Care Plant (Packing Division). Using a quantitative causality approach, data were collected through questionnaires from 66 respondents, representing the entire population in the packing section. Data analysis was performed using Partial Least Square (PLS) with SmartPLS software. The results showed that leadership style, reward, and organizational commitment have a positive and significant direct effect on performance. Leadership style was also found to have a significant effect on organizational commitment, which subsequently acts as a mediator in enhancing performance. However, a unique result was found regarding the reward variable, where organizational commitment failed to mediate the effect of reward on performance. Based on these findings, it is recommended that management redesign the reward system so that it is not only transactional-financial but also incorporates non-financial aspects to foster emotional loyalty. Additionally, it is necessary to strengthen managerial competencies for front-line leaders to create a work culture capable of internalizing organizational goals into personal employee commitment for sustainable performance.